Peut-on redresser la natalité ? - Henripin, Jacques (Assurances)

(untitled) (HEC Montréal, 1989)
The following study by our collaborator Jacques Henripin from the University of Montreal is interesting from several points of view. First he presents the demographic situation in Quebec which, without being alarming, is worrisome. He then examines how to increase the birth rate in Quebec, what role the government and parents should play, can effective policies be adopted, what is the basis of a good family policy. The author concludes we must above all be wary of makeshift solutions.